Effect of Media Combination Treatment on Seedling of Tumih (Combretocarpus rotundatus (Miq.) Danser) Growth - Istomo Istomo; Niechi Valentino (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
Tumih which has a Latin name Combretocarpus rotundatus (Miq.) Danser) is one of the species that lives in peat swamp forests. C. rotundatus often found in secondary forests or forests with open canopies. Nowadays deforestation often occurs in Indonesia, it is feared this species will be decrease and lead to scarcity in natural forest. C. rotundatus also has characteristic that suit for plan in effort to initiate rehabilitation of agitated peatlands. Efforts to propagate this species was applied by the stump method. The research conducted aims to determine the life and growth of tumih by giving the media combination regulators. The results showed that the percentage of life that is obtained for K1 at 86,67%, 80,00% of K2, K3 of 35,56%, K4 at 62,22%, K5 at 71,11%, and 86,67% for K6. Other factors that may affect it is initial height of plants and environmental conditions in research.